Reflection of the arts of psychology in the structure of Dildar's poetic texts - حسین, ئاتا رشید; عبداهلل, عباس صالح (Sulaimani Journal for Humanities, 2025)
The Reflection of Rhetorical Arts in the Structure of Dildar`s Poems. The title of this study is the analysis of poetical texts by the poet Dildar from the perspective of rhetorical arts. Rhetorical arts are considered pivotal with Dildar especially when it comes to dealing with poetic texts considering that rhetorics in Kurdish literature has taken long strides forward in the past few decades. The study consists of an introduction ,two parts as well as results and reference list. The first chapter deals with the concept and definitions of rhetorical arts focusing mainly on eloquence , style and meaning. The second part, however, is intended to analyze thoroughly the poet`s poetic texts from the standpoint of the rhetorical arts.